Issues of Development of Tourist Routes For the Navoiy Region (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article provides information about the tour, tourist route, tourism product and tourism potential of the Navoi region, and the tourist routes organized in it. In addition, the development of new types of tourist routes using modern computer programs is described.